Neonatal Tetanus Evaluation of Treatment and a Proposal for Classification of Severity - Tjandra Husada; T. H. Rampengan; Ign. Harjanto; I. D. Arif; Muzief Munir (Paediatrica Indonesiana, 1976)
An evaluation was made on 22 neonates with Tetanus Neonatorum (age 5 - 21 days), who were admitted to the Military Hospital, Teling, Manado, in 1973. Seventeen of our patients were babies born in their homes and were delivered by the "dukun kampong"; 5 babies were born in the maternity clinic and were helped by midwives. The therapy given were : Anti-Tetanus serum 10,000 U, single dose, given immediately on admission. Procain Penicilline 100,000 U/kg. b.w./day; i.m. divided into 2 equal doses for 10 days. Diazepam (valium) 5 mg./kg. b.w./day; oral, divided into 8 equal doses, and 2.5 mg, parenterally 4 times a day.